PENGARUH STRATEGI PEMBELAJARAN PAILKEM DENGAN MEDIA ANIMASI TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN 3 KEDUNGBANTENG TAHUN AJARAN 2015/2016 - Titik Suparminingsih (Universitas PGRI Madiun, 2016)
Low student learning outcomes in science subjects is because teachers in the field using conventional learning strategies, so that students feel bored and not in the spirit of the learning process. Therefore, the teachers are required to be able to choose an effective learning strategies and efficient. This study aims to determine whether or not the influence of learning strategies PAILKEM with animated media for learning outcomes IPA grade IV SDN Kedungbanteng 3 City Ponorogo in academic year 2015/2016. This research is a quantitative research using experimental methods. This study research design static two groups. The sample selection using saturation sampling technique that is all class IVA and IVB with the number of 27 students per class. The data collection technique using the test method to learn science student outcome data. Data were analyzed with the average difference test (t-test) were previously performed tests of normality and homogeneity test. The results of t-test analysis showed that the value t_hitung = 3.098961 and t_tabel = 1.703 and significance level of 5% t_hitung> t_tabel then H_0 rejected concluded that received H_0 H_a rejected and accepted. so it can be concluded that the learning outcomes of students in the class who were treated using learning strategies PAILKEM with animation media better than the class that is not treated with the use of learning strategies PAILKEM with animation media. This means that there is a significant effect on student learning outcomes with the application of learning strategies PAILKEM with animation media in science subjects subject matter